2009
DOI: 10.1111/igc.0b013e3181a83749
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Receptor Regulates MT1-MMP and MMP-2 Synthesis in SiHa Cells via Both PI3-K/AKT and MAPK/ERK Pathways

Abstract: Matrix metalloproteinase 2 (MMP-2) and membrane type 1 matrix metalloproteinase (MT1-MMP) have been identified as important participants in tumor invasion, metastasis, and angiogenesis. Membrane type 1 matrix metalloproteinase has also been recognized as a major activator of MMP-2. The purpose of this study was to investigate epidermal growth factor (EGF) mediating signal pathways in the regulation of MMP-2 and MT1-MMP in SiHa cells, a cervical cancer cell line. We showed here that EGF induced the expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…It was previously demonstrated by the present authors that EGFR regulates MT1-MMP and MMP-2 synthesis in SiHa cells via both the PI3-K/AKT and MAPK/ERK pathways in SiHa cells (22). To further indicate a role for EGFR in the synthesis and function of other MMP members in SiHa cells, the changes in MMP-1 expression were investigated at the mRNA and protein levels following EGF treatment in the present study.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…It was previously demonstrated by the present authors that EGFR regulates MT1-MMP and MMP-2 synthesis in SiHa cells via both the PI3-K/AKT and MAPK/ERK pathways in SiHa cells (22). To further indicate a role for EGFR in the synthesis and function of other MMP members in SiHa cells, the changes in MMP-1 expression were investigated at the mRNA and protein levels following EGF treatment in the present study.…”
Section: Resultsmentioning
confidence: 62%
“…Our analyses previously demonstrated that EGFR regulates melatonin receptor type 1A (MT1)-MMP and MMP-2 synthesis in the SiHa cervical cancer cell line via both the PI3-K/AKT and MAPK/ERK pathways (22). However, the effects of EGFR localization to lipid rafts on signaling pathways involved in the regulation of MMP-1 expression are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we examined the activation states of various signalling molecules related to cell growth, including ERK, AKT and NF-κB. Activation of these signalling pathways is also involved in metastasis (21)(22)(23)(24). As expected, these signalling molecules were seemed to be more activated by phosphorylation in A549 cells than in H460 cells (Fig.…”
Section: Fibulin-3 Inhibits Signalling Pathways Involved In Cell Growthmentioning
confidence: 68%
“…Because MMP14 and MMP2 have been identified as important participants in tumor cell invasion [27], we have examined whether OT-induced invasiveness of Hec-1-A cells also occurs via these two matrix metalloproteinases. We found that resting Hec-1-A cells expressed detectable levels of both MMP14 and MMP2, but exposure to OT induced an upregulation of their transcripts (Fig.…”
Section: Ot-mediated Up-regulation Of Mmp14 and Mmp2 Are Ptgs1-and Ptmentioning
confidence: 99%